Applying Cynefin framework to explore the experiences of engineering educators undertaking 'emergency remote teaching' during the COVID-19 pandemic. Issue 1 (2nd January 2022) - Caldera, Savindi; Desha, Cheryl; Dawes, Les
ABSTRACT: Higher Education Institutions around the world are all facing the challenge of delivering coursework online. Following a decade of evolving online education options, in 2020 'Emergency Remote Teaching' emerged as an accelerated intervention to enable the rapid implementation of wholly online coursework delivery during the COVID-19 crisis. There is ongoing uncertainty about how to ensure quality offerings in such online learning environments, to meet national and international programme accreditation requirements. The authors undertook an exploratory study of engineering educator experiences with online curriculum delivery during the COVID-19 crisis. The Cynefin framework was used to conceptualise a structured narrative for considering the institutional context likely to be present in a given crisis, to then provide a pathway for educators to consider curriculum delivery options where the pedagogical tools must be changed but the underlying desired competency development remain unchanged. Semi-structured interviews with educators were conducted to help appreciate the spectrum of challenges faced in one university. Synthesising the findings, we present a summary of ERT concerns and opportunities to support educators in rapid curriculum renewal during times of crisis. We conclude the significant opportunity to replicate this study's exploration with a larger sample size, to manage online curriculum renewal going forward.